Prevalence of Pregnancy-Induced Hypertension and Its High-Risk Factors among the Antenatal Women - John, Sony; Vanitha, M.; Babu, Athira; Sushma, Priya; Regina, Ashihrii Eloni; Frank, Reena Wilma (Journal of Health and Allied Sciences NU, 2021)
Objective A hypertensive disorder during pregnancy seriously endangers the safety of the fetus and women during pregnancy. This study was conducted to estimate the prevalence of pregnancy-induced hypertension (PIH) and its risk factors among antenatal women. The aim of this study was to find the prevalence of PIH and risk factors for PIH among antenatal women in a selected hospital in Mangaluru.Methods A descriptive study was performed. The study used the total sample size of 400 pregnant women attending the obstetrics and gynecology outpatient department according to the inclusion and exclusion criteria in a tertiary care hospital in Karnataka. The data was collected with a self-reported checklist. Data were entered and analyzed by using SPSS 23.Results The prevalence of PIH was 10.75% that is 43 antenatal women out of 400. In this study, 34.88% had a family history of PIH, 23% had a previous history of PIH, 16% had a history of gestational diabetes, and 20.93% had a history of thyroid problems. The most important risk factors found for PIH in the present study are the previous history of PIH (adjusted odds ratio [OR] = 1.276, 95% confidence interval [CI: 0.125–11.836), family history of hypertension (adjusted OR=1.930, 95% CI: 1.130–3.296), and thyroid problems (adjusted OR=1.904, CI: 0.786–4.611).Conclusion PIH is a common medical disorder associated with pregnancy. We noted that PIH is more prevalent in those who had it in their previous pregnancy. PIH is associated with multiple complications in the mother and the baby and particularly preterm delivery. The timely intervention of regular antenatal checkups, nutrition, health education, etc., can reduce the severity of PIH.
Keywords: prevalence; risk factors; pregnancy-induced hypertension; antenatal